In search of a “New Grammousta”. Cultural heritage of Aromanians/Vlachs shepherds in the southern Pirine in Bulgaria (I) - Kocój, Ewa; Kocój, Łukasz (Balcanica Posnaniensia. Acta et studia, 2022)
In search of a “New Grammousta”: Cultural heritage of Aromanians/Vlachs shepherds in the southern Pirine in Bulgaria (I). The history and cultural heritage of the Aromanian (Vlach) shepherds in Bulgaria is a challenging topic that requires particular inquisitiveness in scientific research. The Aromanians arrived there after years of severe persecution perpetrated by the Turks and Albanians at the end of the 18th century. In the high mountains, they created their own world, which became their refuge for decades, with settlements comprising houses, farms, places of religious worship, and pastures. They set up a network of stakeholders who purchased their goods. Due to their specific lifestyle and the oral nature of their culture, the historical and ethnographic sources illustrating their world are scarce. This paper is to present the history of the Aromanian/Vlach community from the moment they settled in the Pirin Mountains in Bulgaria in the 19th century until they left Bulgaria in the first half of the 20th century. It describes the main Aromanian settlements, including their location, traditional professions, wintering places, and the crucial herding routes in this region.